2018
DOI: 10.1134/s1607672918030031
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Geometric Isomers of Etherolenic Acid—the Products of Plant Lipoxygenase Cascade

Abstract: Data on the influence of the double bond geometry on the antimicrobial properties of different isomers of etherolenic acid against phytopathogenic bacteria are presented. (ω5Z)-Etherolenic acid possesses bactericidal properties against Xanthomonas campestris ssp. vesicatoria, Pseudomonas syringae ssp. tomato, Pectobacterium atrosepticum SCRI1043; the etherolenic and (11Z)-etherolenic acids possess only bacteriostatic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Also, cis forms may induce greater membrane deformation than trans forms. In addition, conjugated cis bonds activation energy is lower and, apparently, more active against pathogens than monounsaturated FA [77].…”
Section: The Road To the Next Levelmentioning
confidence: 99%
“…Also, cis forms may induce greater membrane deformation than trans forms. In addition, conjugated cis bonds activation energy is lower and, apparently, more active against pathogens than monounsaturated FA [77].…”
Section: The Road To the Next Levelmentioning
confidence: 99%
“…The last group of enzymes, DESs, is apparently the last of the described evolutional acquisitions of plants. DESs produce antimicrobial and fungicide compounds, divinyl ethers [20,45,150,151]. DESs are detected in several plant species that are phylogenetically distant from each other.…”
Section: Correlation Between Primary Structure and Catalytic Activity...mentioning
confidence: 99%
“…These branches are less studied. The literature describes the participation of divinyl ethers in protection against a number of pathogens: bacteria [ 18 ], oomycetes [ 19 ] and fungi [ 20 ]. The cloning and characteristics of several AOSs, HPLs, DESs and EASs from different plant species revealed that they are closely related members of the cytochrome P450 family, and form the CYP74 family, which is specialized in the metabolism of hydroperoxides [ 21 ].…”
Section: Introductionmentioning
confidence: 99%